Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture